PERCEPTION OF PROTECTIVE MEASURES AMONG PATIENTS TESTED FOR COVID-19: A CROSS SECTIONAL STUDY CONDUCTED IN THE SERBIAN UNIVERSITY CENTER - Aleksandar (Acta medicae Medianae, 2022)
The main objective of this study was to explore the practical benefits of precautionary behaviors among general population considering the Coronavirus disease 19 (COVID-19) infection rates. Additionally, sociodemographic aspects, related with the COVID-19 transmission, were also of interest. For the purposes of this research, we have selected two groups of respondents who voluntarily agreed to participate. The research was conducted in the period from October to December 2020 at the Faculty of Medicine of the University of Niš (Serbia). A total of 1,035 people underwent a telephone survey. There were 522 (50.4%) women and 513 men; 630 (60.9%) were infected with corona virus. The obtained results indicate that age, level of education, self-assessed health and the existence of chronic diseases have a significant impact on the self-perceived risk of contracting COVID-19 infection. Moreover, the presence of the so-called "fear factor" has a significant impact on infection rates. In contrast, no effect of gender difference and wearing mandatory protective masks was observed on COVID-19 infection rates. This study yields novel insights into common protective measures against COVID-19, highlighting differences between the studied protective factors. Further efforts in this direction are required in order to develop more elaborate, well-balanced, efficient strategies for containing the ongoing pandemic, especially in the context of the contagion control.